MASA DEPAN PRODI VOKASI KEUANGAN DAN PERBANKAN DI ERA NEO BANK DAN MERDEKA BELAJAR - Teddy Richendi; Slamet Soesanto (ITB Swadharma, 2021)
Vocational education is education that emphasizes the importance of the profile of its graduates having certain skills that are specifically designed to meet the needs of industry as workers or as entrepreneurs. The massive use of information technology in the financial and banking industries has made it easier for people to transact business. The process of financial transactions involving a lot of human intervention can now be replaced by machines (technology). So it becomes a necessity that cannot be avoided by the banking finance study program so that it immediately adapts, where the graduate profile is prepared to be compatible with the needs of the industry. In the context of